A two-layer nested game for an active energy community including shared energy storage and multiple prosumers under renewable portfolio standards - Yaxin Tan; Weisheng Xu; Zhiyu Xu; Ruining Tong; Yuanbo Zhang (International Journal of Electrical Power & Energy Systems)
The renewable portfolio standards (RPS) offers a promising solution to the challenge of high-level penetration of renewable energy into the next-generation power grid. The shared energy storage (SES) has emerged as a crucial innovation that significantly aids prosumers in fulfilling RPS requirements. This paper proposes a two-layer nested game model to capture the interactions between SES and prosumers in an active energy community, and with the external main grid, hydropower station, and wind farm. In the upper layer, a Stackelberg game model is established, in which SES acts as the leader maximizing profit by offering electricity prices, while the alliance of prosumers is the follower responding to the prices through demand response and peer-to-peer (P2P) energy exchange. In the lower layer, a cooperative game is constructed for the prosumer alliance, the contributions of individual prosumers are scored and the asymmetric Nash bargaining is utilized to fairly allocate the total expense within the prosumer alliance. The alternating direction method of multipliers (ADMM) is adopted for privacy protection. A case study of a real active energy community in Southwest China demonstrates effectiveness and robustness of the proposed model under diverse conditions. The computational results also confirm the model achieves greater stability, reduces prosumers’ expenses, and mitigates the dependence on SES.